Model Pendidikan Jihad Pondok Pesantren Ta'mirul Islam Surakarta 2014-2015 - Maksum, M Nur Rochim; , Dr. Abdullah Aly, M.Ag; , Drs. Abdullah Mahmud, M.Ag (2015)
ABSTRACT EDUCATION MODEL COTTAGE BOARDING TA'MIRUL ISLAMIC JIHAD SURAKARTA 2014-2015 M Nur Rochim infallible, G000130176, Department of Islamic Education (MT) Faculty of Islamic Studies, University of Muhammadiyah Surakarta. The purpose of this study was to determine the meaning of jihad according to Ta'mirul Islamic boarding school and education models applied jihad Ta'mirul Surakarta Islamic Boarding School from 2014 to 2015. This type of research is a field research with qualitative methods with primary and secondary data sources, ie data taken directly from the resources Ta'mirul Islamic boarding school leadership, care staff Ta'mirul Islamic Boarding School and Boarding School Ta'mirul Islam, this data collection technique using interviews, observation and documentation. Data analysis technique used is the deductive method, which is a way of thinking which is still a research tool since choosing, finding the problem of constructing a hypothesis, and conduct field observations to test the data. These results indicate that: 1) Boarding Ta'mirul interpret Islam in jihad in accordance with the theory of Joseph Qordowi as a form of earnestness in doing something, as the meaning of the language of jihad which is derived from the word "jahada-yajhadu" truly meaningful besungguh , The Islamic Boarding School Ta'mirul avoid the sense of narrowing the meaning of jihad is the jihad which means war, and Islamic Boarding School Ta'mirul split into three namely jihad: jihad with power, with the spirit of jihad (the heart) and the jihad with the mind. Educational model applied jihad Islamic Boarding School Ta'mirul namely: 1. Jaulah 2. mujahadah 3. Education 4. 5. Jihad economic social Jihad 6. Education organization. Keywords: Ta'mirul Islam, education jihad, meaning, models.